Children Social, Emotional, language Development: - Majumdar, Ananda (IJRDO - Journal of Social Science and Humanities Research, 2017)
Purpose of this article is to explore child mind through their various stages of development, from birth to age eight children’s need immediate development of social, physical, emotional, psychological, moral to avoid challenges in their life, without these development children’s can be unsocial, violent, harsh, misbehaved, physically disable and due to those challenges they will not be able to independent in their life and finally an incomplete human being without social value, we see violent, killings people by teenagers and so on, this is because of improper development in their childhood which is crucial stage in their life for rest of their life, therefore families, caregivers, teachers, peer groups, media need to be very careful on their society, civilized community and about their children’s. Children’s are the future of community, society and the country, if they are properly developed then it is good for overall scenario but if they are not get proper training, treatment then it is a problem and it can be violent for the society, community and for the country.